The Effectiveness of Range Of Motion (ROM) Exercises in Reducing Pain and Improving Social Function in Patients with Knee Osteoarthritis - Nurhayati, Nurhayati; Ritawati, Ritawati; Syamsuddin, Asniah; Warnidar, Eka; Riani, Eka Oktarina; Isneini, Isneini (Labor Program Studi Pendidikan Sosiologi, 2024)
This study aims to analyze the effectiveness of Range of Motion (ROM) exercises in reducing pain and improving social function in patients with knee osteoarthritis, and to identify factors that influence the success of ROM program implementation. The study used a qualitative approach with a systematic literature study method. Data were collected through searches in the electronic databases PubMed, Scopus, and CINAHL with the inclusion criteria of primary research articles in 2019-2024. Data analysis was carried out thematically using NVIVO software and quality assessment using the Mixed Methods Appraisal Tool. An effective ROM program includes a duration of 30-45 minutes per session with a frequency of 3-4 times per week, showing a significant decrease in pain after 4-6 weeks of implementation. Improved social function is seen through active participation in community activities and better social interactions. Key success factors include program personalization, early professional supervision, and family support. Understanding of the effectiveness of ROM is reinforced by nursing and sociological theories that emphasize the importance of a holistic approach in the management of knee osteoarthritis.